2009
DOI: 10.1063/1.3176499
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the temperature characteristics of InAs/GaAs quantum dot lasers

Abstract: A systematic investigation of the temperature characteristics of quantum dot lasers emitting at 1.3 m is reported. The temperature dependence of carrier lifetime, radiative efficiency, threshold current, differential efficiency, and gain is measured, and compared to the theoretical results based on a rate equation model. The model accurately reproduces all experimental laser characteristics above room temperature. The degradation of laser characteristics with increasing temperature is clearly shown to be assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
2
12
1
Order By: Relevance
“…The out-scattering of charge-carriers thus becomes more probable at elevated charge-carrier temperatures [URA02,ROS09a]. Note that in the derivation of above expressions, only a quasi-equilibrium within the quantum well must be assumed without making assumptions about the quantum-dot occupations.…”
Section: Charge-carrier Scattering In Quantum-dot Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The out-scattering of charge-carriers thus becomes more probable at elevated charge-carrier temperatures [URA02,ROS09a]. Note that in the derivation of above expressions, only a quasi-equilibrium within the quantum well must be assumed without making assumptions about the quantum-dot occupations.…”
Section: Charge-carrier Scattering In Quantum-dot Structuresmentioning
confidence: 99%
“…An increase in lattice and chargecarrier temperature often leads to reduced efficiency and diminished device performance [KLO99,ROS09a]. On the other hand, higher temperatures were shown, e.g., to improve the performance of mode-locked laser devices [CAT07].…”
Section: Quantum-dot Laser Carrier-heating Modelmentioning
confidence: 99%
“…The out-scattering of chargecarriers thus becomes more probable at elevated charge-carrier temperatures [34,35]. Note that in the derivation of above expressions, only a quasi-equilibrium within the quantum well must be assumed without making assumptions about the quantumdot occupations.…”
Section: Detailed Balancementioning
confidence: 99%
“…10,11 Rossetti et al 10 suggest that the increase in threshold current with temperature is due to thermal escape of carriers followed by monomolecular ͑defect related͒ NR recombination in the wetting layer ͑WL͒ 11 also suggested that the use of power laws to describe the recombination processes in QDs may not be a valid approach. Previous work by Marko et al…”
mentioning
confidence: 99%
“…The decrease in threshold current with increasing pressure is due to decreasing NR recombination ͑since radiative recombination at this temperature accounts for only 6% of the total threshold current͒. Rossetti et al 10 argued that the decrease in threshold current as a function of pressure is due to an improvement in optical confinement, and hence a corresponding decrease in threshold gain with increasing pressure.…”
mentioning
confidence: 99%